Is a bio-psychosocial approach model possible at the first level of health services in the Democratic Republic of Congo? An organizational analysis of six health centers in South Kivu - Christian Eboma Ndjangulu Molima; Hermès Karemere; Samuel Makali; Ghislain Bisimwa; Jean Macq (BMC, 2023)
Abstract Background The health system, in the Democratic Republic of Congo, is expected to move towards a more people-centered form of healthcare provision by implementing a biopsychosocial (BPS) approach. It's then important to examine how change is possible in providing healthcare at the first line of care. This study aims to analyze the organizational capacity of health centers to implement a BPS approach in the first line of care. Methods A mixed descriptive and analytical study was conducted from November 2017 to February 2018. Six health centers from four Health Zones (South Kivu, Democratic Republic of Congo) were selected for this study. An organizational analysis of six health centers based on 15 organizational capacities using the Context and Capabilities for Integrating Care (CCIC) as a theoretical framework was conducted. Data were collected through observation, document review, and individual interviews with key stakeholders. The annual utilization rate of curative services was analyzed using trends for the six health centers. The organizational analysis presented three categories (Basic Structures, People and values, and Key Processes). Result This research describes three components in the organization of health services on a biopsychosocial model (Basic Structures, People and values, and Key processes). The current functioning of health centers in South Kivu shows strengths in the Basic Structures component. The health centers have physical characteristics and resources (financial, human) capable of operating health services. Weaknesses were noted in organizational governance through sharing of patient experience, valuing patient needs in Organizational/Network Culture, and Focus on Patient Centeredness & Engagement as well as partnering with other patient care channels. Conclusion This study highlighted the predisposition of health centers to implement a BPS approach to their organizational capacities. The study highlights how national policies could regulate the organization of health services on the front line by relying more on the culture of teamwork in the care structures and focusing on the needs of the patients. Paying particular attention to the values of the agents and specific key processes could enable the implementation of the BPS approach at the health center level.